(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the ethical and philosophical motifs in the prose of Valentin Rasputin and Khurshid Dustmukhammed. A comparative analysis of the works of the two authors is conducted, revealing similarities and differences in their approaches to issues of morality, spirituality, and human responsibility towards society and nature. Special attention is given to the questions of human conscience, duty, compassion, as well as ecological and social responsibility. The study highlights how the writers reflect national traditions and worldview aspects in their works, embodying the cultural and philosophical characteristics of their peoples. The paper contributes to a deeper understanding of the role of ethical and philosophical values in literature and their significance in the modern world.